Loneliness and Depression in Self-Care Students in Mashhad Northeastern Iran - Samaneh Sadat Fattahi Massoom; Hossein Salimi Bajestani (Shiraz University of Medical Sciences, 2016)
Background: Who takes care of the children after school? is a question in many researches. Children may feel lonely and depressed if they open the house door and find no body in the house. Objectives: The study examines loneliness and depression in students who regularly care for themselves after school (latchkey students) and compared with students who enjoy the parent's company. Patients and Methods: This study comprised 270 students, aged between 7 to 13 years in Mashhad, selected by convenience and cluster random-assignment sampling, using depression self-rating questionnaire and loneliness self-rating scale. Results: Using a causal-comparative research method, independent t-test results showed significant differences in loneliness (-4.32, P ≤ 0.05) and depression (-3.02, P ≤ 0.05) between latchkey and non-latchkey students. Using the Pearson correlation test, significant correlation between depression and loneliness was observed among latchkey students (r = 0.59, P ≤ 0.05). However, no significant difference between loneliness and depression was observed (r = 0.02. P ≥ 0.05) in non-latchkey students. Multiple regression analysis also showed that depression variance can be determined by gender 22% and loneliness 34% (boys and girls). Conclusions: The findings of this study, specifically the significant difference between latchkey and non-latchkey children, regarding feelings of loneliness and depression, carries clear message for parents. It can be concluded that mothers who spend most of their time working out of the house and deprive their children of their presence at home may cause some form of mental distress like loneliness and depression in youngsters. Moreover, gender differences affect the degree of these psychological disorders.